El discurso sobre la identidad mestiza en la historiografía finisecular mexicana de la arquitectura - Johanna Lozoya (Les Cahiers ALHIM)
AbstractThis articles deals with nationalist identitary issues in contemporary Mexican historiographies of architecture, such as the mestizo nature of the so called mexicanidad. This cultural and ideological modern conviction of a true Mexican architecture based on biocultural fusion of different and antagonic atemporal attributes of two races, has developed through an essentialist, and not historical, mental approach towards the constitution of nation in the XXth century. This text points out that the myth of the mestizo identity in architecture can´t support itself nowadays, when multiple identitary forms expressing throughout the nation shows that though it was imagined homogeneous in the XXth century, Mexico is considerably multicultural.